Factors Influencing Birth Preparedness and Complication Readiness among Post-Natal Women in Selected Primary Health Centers in Ibadan, Nigeria (2023)
Background: Birth preparedness and complication readiness is a strategic intervention to achieve a reduction in the rate of maternal mortality. However, despite the importance and ease of use of this intervention, it has been observed that several factors have hindered the practice. Hence, the need to consider the knowledge, attitude, practice, and factors that influences Birth preparedness and Complication readiness among post- natal women. Method: This descriptive cross-sectional study used a multi-stage sampling technique to select 116 post-natal women in selected primary health centers in Ibadan North Local Government Area, Oyo state. An adapted structured questionnaire was used to assess the knowledge, attitude, practice and factors influencing the practice of birth preparedness and complication readiness. Statistical analysis was done using Statistical Package for the social science (SPSS) version 21.0 software. Descriptive data were presented as frequency and percentages while the chi-square test was used to test the hypotheses at P value < 0.05. Result: The majority of respondents were highly knowledgeable (86.2%). The respondents had a positive attitude towards birth preparedness and complication readiness (75%). The practice level was high among the respondents (71.6%). However, the factors that influenced practice were lack of adequate knowledge (X2-4.578, P=0.032), pre-mature delivery (X2-19.929, P=0.000) and environmental insecurities (X2-6.556, P=0.010). Conclusion: There is a relationship between factors (lack of adequate knowledge, premature delivery and environmental insecurities) and the practice of birth preparedness and complication readiness. Hence, measures should be employed to address the identified factors to improve the practice of birth preparedness and complication readiness.